Hegemon's tool kit: US leadership and the politics of the nuclear nonproliferation regime - Gibbons, Rebecca Davis (New York, USA: Cornell University Press, 2022)
"Rebecca Davis Gibbons argues that the nuclear nonproliferation regime is a fundamental part of the US-led global ordering project, that Washington, DC, has long persuaded other states to join this regime such that a decline in US relative power could result in nuclear proliferation"--
Introduction : Understanding Adherence to the Nuclear Nonproliferation Regime -- Explaining Adherence to the Nuclear Nonproliferation Regime -- How the United States Promotes the Nuclear Nonproliferation Regime -- Slow but Successful US Promotion of the NPT -- The Hard-Fought Battle for NPT Extension -- Mixed Success in Promoting a New Safeguards Agreement -- Conclusion : Maintaining the Regime in a Changing Global Order.
Includes bibliographical references and index.
Keywords: Treaty on the Non-proliferation of Nuclear Weapons -- (1968 June 12); Nuclear nonproliferation -- Political aspects; Nuclear arms control -- Political aspects; Nuclear weapons -- Political aspects; Nuclear nonproliferation -- Government policy -- United States; Nuclear arms control -- Government policy -- United States; Nuclear weapons -- Government policy -- United States; Nuclear nonproliferation -- International cooperation; Security, International